Smart Charity Box with ESP32 and Chatbot - Zuhriyah, Nur Anjumi; Rosyadi, Saadilah (Journal of Robotics, Automation, and Electronics Engineering, 2024)
The purpose of this project is to: (1) Create a security system tool on the door of the charity box at the Al Huda Mosque, Sirau Village, Kemranjen, Banyumas using the ESP32 microcontroller. (2) Know the function of all components used such as the ESP32 microcontroller, RFID, servo motor and ultrasonic sensor. (3) Know the performance test of Telegram to control the smart charity box project. Based on the design results, it shows that: (1) Produce a smart charity box tool using ESP32 components, ultrasonic sensors, RFID and servo motors as door drivers. The features it has can detect the remaining height of the charity box space and access the door via the RFID module or Telegram bot. (2) The results of functional tests on each component, both hardware such as ESP32, RFID, ultrasonic sensors, servo motors or software, can work well. (3) The results of the performance test show that this project can detect the remaining height of the space in the charity box and open the door by tapping the RFID card or accessing the Telegram bot.